EFFECT OF FERMENTATION TIME AND ROASTING TEMPERATURE ON THE SENSORY, CHEMICAL, AND PHYSICAL CHARACTERICTICS OF WINE COFFEE ROBUSTA TIRTOYUDO - Maligan, Jaya Mahar; Zefanya Anggono, Nathania (Jurnal Pangan dan Agroindustri, 2023)
The purpose of this study was to determine the effect and results of the best treatment of the factors of fermentation time and roasting temperature, and to determine the physical and chemical quality characteristics of the resulting Robusta Tirtoyudo wine coffee. The experimental design used is Factorial Randomized Group Design and data will be analyzed with ANOVA. The results showed that fermentation time and roasting temperature had a significant effect on fragrance, flavor, acidity, body, and overall attributes. Fermentation time also affects the aftertaste, while the interaction between the two treatment factors significantly affects flavor, body, and overall. Roasted beans had a normal aroma, taste, and color, moisture content below 7%, and ash content below 5%. The best wine coffee was obtained from a 30 days fermentation - medium roast (150˚C), which had an ash alkalinity 62.16 ml NaOH/100g, coffee extract 12.61%, caffeine 4.23% and cupping score 83.30 (specialty).